Analysis of Attitude Errors in GRACE Range-Rate Residuals-A Comparison Between SCA1B and the Fused Attitude Product (SCA1B + ACC1B) - Goswami, Sujata; Klinger, Beate; Weigelt, Matthias; Mayer-Gurr, Torsten (IEEE sensors letters, 2018)
For missions such as GRACE, precise knowledge of the satellite's attitude is a fundamental requirement for the realization of the intersatellite ranging principle. It is not only essential for the realization of the precise in-orbit intersatellite pointing but also for the recovery of accurate temporal gravity field models. Here, we present a comparative study of two attitude datasets. One of them is the standard SCA1B RL02 datasets provided by JPL NASA, and another is a fused attitude dataset computed at TU Graz, based on the combination of ACC1B angular accelerations and SCA1B quaternions. Furthermore, we also present the impact of the attitude datasets on the intersatellite range measurements by analyzing their residuals. Our analysis reveals the significant improvement in the attitude due to the reprocessed product and reduced value of residuals computed from the reprocessed attitude.